Association between autonomic function and obstructive sleep apnea: A systematic review. (June 2021) - Dissanayake, Hasthi U.; Bin, Yu Sun; Ucak, Seren; de Chazal, Philip; Sutherland, Kate; Cistulli, Peter A.
Summary: Obstructive sleep apnea (OSA) is an independent risk factor for hypertension and cardiovascular disease. Effects of OSA on the autonomic nervous system may mediate this association. We performed a systematic literature review to determine the profile of autonomic function associated with OSA. Three electronic databases were searched for studies of OSA patients aged ≥18 years in which autonomic function was assessed. Studies comparing patients with and without OSA, or examining the association of OSA severity with changes in autonomic function were included. Seventy-one studies met the inclusion criteria and autonomic function has been assessed using a range of techniques. The profile of autonomic function found in OSA include increased sympathetic activity, reduced parasympathetic activity and less consistently found low heart rate variability. Altered autonomic function in OSA may explain the pathophysiology of increased cardiovascular risk. Evidence from intervention studies is required to determine if treatment improves autonomic function associated with OSA.